Towards multivalent CD1d ligands: synthesis and biological activity of homodimeric α-galactosyl ceramide analogues. - Jervis, P; Moulis, M; Jukes, J; Ghadbane, H; Cox, L; Cerundolo, V; Besra, G (2012)
A library of dimeric CD1d ligands, containing two α-galactosyl ceramide (α-GalCer) units linked by spacers of varying lengths has been synthesised. The key dimerisation reactions were carried out via copper-catalysed click reactions between a 6"-azido-6"-deoxy-α-galactosyl ceramide derivative and various diynes. Each α-GalCer dimer was tested for its ability to stimulate iNKT cells.